Problematika Naskah Sejarah di Dunia Melayu: Antara Mitos dan Realita (Studi Kasus Hikayat Raja Pasai) - 'Afifah, Nurul (MOZAIK Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2024)
One of the challenges that historians and philologists face is analyzing historical texts, especially traditional historiographic works like 'babad' and 'hikayat,' which may have been added to or subtracted from in various aspects. Such manuscripts cannot be considered the primary reference source for constructing a chronological history, as they lean more towards historical literature constructed from the author's imagination. This article discusses the challenges posed by Malay manuscripts that contain elements of myth and imagination. The study takes a case example of the manuscript "Hikayat Raja Pasai". The objective is to examine the position and role of hikayat or traditional historiography in general concerning the narration of history and its acceptance as a historical source. The research employs a descriptive-analytical method through several stages, including: 1) manuscript selection, 2) literature review, 3) content analysis and identification of imaginative elements in the manuscript, 4) examination of history to verify the accuracy of information, 5) interpretation of results, 6) writing, and 7) drawing conclusions. From this study, it was found that despite containing myths, hikayat still plays a role as a means to showcase the character of a community, aiding readers in understanding a belief, and myths are often more effective in raising human awareness and guiding them towards improvement. However, in accepting hikayat as a historical source, a critical and selective approach is necessary. Therefore, the application of historical methods is crucial to identify which elements can be used as historical sources and which ones should be considered purely imaginative.